REALITAS BAHASA SLANG DI KALANGAN GENERASI Z: IMPLIKASI TERHADAP PENGGUNAAN BAHASA INDONESIA MODERN - Sari, Irna Revita; Mikdad, Mikdad; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This research explores the reality of slang language use among Generation Z and its implications for the development of modern Indonesian. Slang, which was initially only used in informal contexts, is now an integral element in Generation Z's daily communication. Based on the questionnaire results, the frequency of slang use is very high, with the types of slang dominated by terms from social media, such as “ngab,” “santuy,” or “auto.” Slang is used to create a relaxed atmosphere, show group identity, and increase emotional closeness between users. Nonetheless, the intensity of slang use can pose challenges, such as reduced exposure to standardized language in formal contexts. This study also found that acceptance of slang varies depending on the context of communication, with a tendency for the boundaries between formal and informal language to blur. In the long run, this phenomenon is predicted to enrich the vocabulary of Indonesian while posing a risk to the preservation of linguistic rules. Penelitian ini mengeksplorasi realitas penggunaan bahasa slang di kalangan Generasi Z dan implikasinya terhadap perkembangan bahasa Indonesia modern. Bahasa slang, yang awalnya hanya digunakan dalam konteks informal, kini menjadi elemen integral dalam komunikasi sehari-hari Generasi Z. Berdasarkan hasil kuesioner, frekuensi penggunaan slang sangat tinggi, dengan jenis slang yang didominasi oleh istilah dari media sosial, seperti